Ten questions concerning occupant health in buildings during normal operations and extreme events including the COVID-19 pandemic. (15th January 2021) - Awada, Mohamad; Becerik-Gerber, Burcin; Hoque, Simi; O'Neill, Zheng; Pedrielli, Giulia; Wen, Jin; Wu, Teresa
Abstract: Even before the COVID-19 pandemic, people spent on average around 90% of their time indoors. Now more than ever, with work-from-home orders in place, it is crucial that we radically rethink the design and operation of buildings. Indoor Environmental Quality (IEQ) directly affects the comfort and well-being of occupants. When IEQ is compromised, occupants are at increased risk for many diseases that are exacerbated by both social and economic forces. In the U.S. alone, the annual cost attributed to sick building syndrome in commercial workplaces is estimated to be between 10 billion to 70 billion. It is imperative to understand how parameters that drive IEQ can be designed properly and how buildings can be operated to provide ideal IEQ to safeguard health. While IEQ is a fertile area of scholarship, there is a pressing need for a systematic understanding of how IEQ factors impact occupant health. During extreme events, such as a global pandemic, designers, facility managers, and occupants need pragmatic guidance on reducing health risks in buildings. This paper answers ten questions that explore the effects of buildings on the health of occupants. The study establishes a foundation for future work and provides insights for new research directions and discoveries. Highlights: How buildings influence occupant health (physical, mental and social well-being) is explained. Existing practices, codes, and processes to prevent negative health impacts are reviewed. Social and economic impacts resulting from unhealthy buildings are presented. Lessons learned about health in buildings during the COVID-19 pandemic is presented. Opportunities for future research and discovery to achieve healthy buildings are discussed.